2020
DOI: 10.1002/anie.202010790
|View full text |Cite
|
Sign up to set email alerts
|

CO Binding to the FeV Cofactor of CO‐Reducing Vanadium Nitrogenase at Atomic Resolution

Abstract: Nitrogenases reduce N2, the most abundant element in Earth's atmosphere that is otherwise resistant to chemical conversions due to its stable triple bond. Vanadium nitrogenase stands out in that it additionally processes carbon monoxide, a known inhibitor of the reduction of all substrates other than H+. The reduction of CO leads to the formation of hydrocarbon products, holding the potential for biotechnological applications in analogy to the industrial Fischer–Tropsch process. Here we report the most highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 31 publications
1
74
0
Order By: Relevance
“…Indeed, it has long been proposed that the N 2 ase active site features multiple substrate binding sites and that the formation of these binding sites requires the particular substrate under turnover conditions; that is, the cofactor is dynamic during catalysis [11, 12] . Given the complexity of the N 2 ase active site and the lack of ligand binding to the as‐isolated [7Fe:9S:1C:1Mo]– R ‐homocitrate cofactor form, the nature of substrate (or inhibitor) coordination remained elusive until defined in detail by high resolution structural studies of ligand‐bound Mo and vanadium [V] N 2 ases [2, 10, 13–16] . Evidence for the dynamic behavior of the cofactor was provided by the observation that selenium could be substituted into a specialized group of sulfurs in the FeMo‐cofactor known as the belt sulfides, and could migrate through these positions under turnover conditions [13] …”
Section: Figurementioning
confidence: 99%
“…Indeed, it has long been proposed that the N 2 ase active site features multiple substrate binding sites and that the formation of these binding sites requires the particular substrate under turnover conditions; that is, the cofactor is dynamic during catalysis [11, 12] . Given the complexity of the N 2 ase active site and the lack of ligand binding to the as‐isolated [7Fe:9S:1C:1Mo]– R ‐homocitrate cofactor form, the nature of substrate (or inhibitor) coordination remained elusive until defined in detail by high resolution structural studies of ligand‐bound Mo and vanadium [V] N 2 ases [2, 10, 13–16] . Evidence for the dynamic behavior of the cofactor was provided by the observation that selenium could be substituted into a specialized group of sulfurs in the FeMo‐cofactor known as the belt sulfides, and could migrate through these positions under turnover conditions [13] …”
Section: Figurementioning
confidence: 99%
“…The Fischer–Tropsch‐type chemistry exhibited by nitrogenase suggests that the multimetallic active site can bind more than one ligand simultaneously. The expansion of the Fe6 coordination environment to accommodate a second CO ligand represents a new mode of FeMo‐cofactor ligand binding that complements the displacement of belt sulfurs by ligands that has been previously reported for Mo and V N 2 ases [10, 13, 15, 16, 39] . For CO reduction to hydrocarbons, one might intuit that binding of coupled substrates would occur at one metal center or adjacent metal centers, leading to reductive elimination of the hydrocarbon product.…”
Section: Figurementioning
confidence: 62%
“…In particular, for Mo N 2 ase, methane (CH 4 ) was not detected as a product of CO reduction; rather, higher order hydrocarbons were detected, suggesting that multiple CO‐derived molecules could bind to the FeMo‐cofactor at a time [17] . We reported the initial crystal structure of a ligand bound form of Mo N 2 ase from Azotobacter vinelandii (Av) in which one of the belt sulfides, S2B, of the cofactor is displaced by a carbon monoxide (CO) molecule ( Av1‐CO ); [10] a similar binding mode was subsequently demonstrated for the Av vanadium nitrogenase [16] . Spectroscopic studies have highlighted that several distinct CO‐bound species can be observed under turnover conditions [20–23] .…”
Section: Figurementioning
confidence: 88%
“…In nitrogenase, the details of CO inhibition and CO turnover are only beginning to emerge 36 , but it seems to be clear that the enzyme can bind both bridging and terminal CO ligands ( Figure 2). 72 On the opposite, CO inhibition is an established phenomenon in CcO (Figure 3) and related heme proteins 73 as well as all type of hydrogenases ( Figure 1). 21 For example, in the presence of CO gas, the active-ready Hox state of [FeFe]-hydrogenase with three CO bands converts into the inhibited Hox-CO state with four CO bands.…”
Section: Reactions With Carbon Monoxide Gasmentioning
confidence: 99%
“…Figure 10D illustrates the reaction of dithionite-reduced VFe nitrogenase with CO. Inhibition gives rise to a single, broad IR band at 1931 cm -1 (inset) that immediately vanishes in the absence of exogenous CO. As demonstrated by XRD earlier, a µCO ligands can be assumed (Section 6). 72…”
Section: Reactions With Carbon Monoxide Gasmentioning
confidence: 99%